Comparative Study of Filarial Detection by Microscopic Examination and Serological Assay Utilizing BMR1 and BMXSP Recombinant Antigens for Evaluation of Filariasis Elimination Program at Kampung Sawah and Pamulang, South Tangerang District, Banten, In - Nasution, Silvia (Indonesian Journal of Tropical and Infectious Disease, 2015)
South Tangerang district is one of the endemic areas for filariasis; and based on an evaluation study in 2008-2009 which covered several subdistricts, the prevalence of microfilaria was between 1â2.4%. Nevertheless, the evaluation by serological assay has never been reported. A cross-sectional study was conducted to detect the microfilaremia and anti-filarial IgG4 antibody status in Kp Sawah and Pamulang subdistricts. Cluster sampling was performed in Kp Sawah by collecting finger-prick blood (FPB) and venous blood samples from inhabitants who lived with and nearby the four elephantiasis subjects in the area. The FPB were only collected in Pamulang area by consecutive sampling method. The detection method included microscopic evaluation of FPB and serological detection using recombinant antigens BmR1 and BmSXP by ELISA and lateral flow rapid tests. Symptomatic patients who had 2ndÂ and 3rdÂ degree of elephantiasis were clinically determined in 10% (4/40) subjects. Among those with elephantiasis, 2 were positive serologically but their microscopic results were all negative (40/40). Meanwhile, the microscopic result for 107 subjects from Pamulang were all negative. The results of the rapid tests showed that 15% (6/40) of the positive cases were detected by Brugia Rapid and 27.5% (11/40) by PanLF. Meanwhile, the ELISA showed that 20% (8/40) of the cases were positive with BmSXP, whereas only 2.5% or 1/40 sample was found to be positive with BmR1. Even though the sensitivity of the Rapid test was lower when compared to microscopic examination for these samples, the assay showed good specificity ranging from 72.5 to 97.5%. The optical density (OD) values of ELISA has ranged between 0.3â3.045.